2021
DOI: 10.2147/tacg.s257511
|View full text |Cite
|
Sign up to set email alerts
|

Known Mutations at the Cause of Alpha-1 Antitrypsin Deficiency an Updated Overview of SERPINA1 Variation Spectrum

Abstract: Alpha-1-Antitrypsin deficiency (AATD), caused by SERPINA1 mutations, is one of the most prevalent Mendelian disorders among individuals of European descend. However, this condition, which is characterized by reduced serum levels of alpha-1-antitrypsin (AAT) and associated with increased risks of pulmonary emphysema and liver disease in both children and adults, remains frequently underdiagnosed. AATD clinical manifestations are often correlated with two pathogenic variants, the Z allele (p. Glu342Lys) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 107 publications
(278 reference statements)
1
41
0
Order By: Relevance
“…Alpha-1 antitrypsin deficiency (AATD) is a genetic condition, transmitted by autosomal codominant inheritance, caused by mutations of the SERPIN A1 gene, of which more than 120 variants have been identified, and about 40% of them can cause AATD. 2 The vast majority of SERPIN A1 genotypes result from combinations between the normal protease inhibitor (Pi) M allele and the most frequent deficiency alleles PiS and PiZ, namely PiMM, PiMS, PiSS, PiMZ, PiSZ and PiZZ, which roughly express 100%, 80%, 60%, 55%, 40% and 15% of serum AAT, respectively. 3 , 4…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alpha-1 antitrypsin deficiency (AATD) is a genetic condition, transmitted by autosomal codominant inheritance, caused by mutations of the SERPIN A1 gene, of which more than 120 variants have been identified, and about 40% of them can cause AATD. 2 The vast majority of SERPIN A1 genotypes result from combinations between the normal protease inhibitor (Pi) M allele and the most frequent deficiency alleles PiS and PiZ, namely PiMM, PiMS, PiSS, PiMZ, PiSZ and PiZZ, which roughly express 100%, 80%, 60%, 55%, 40% and 15% of serum AAT, respectively. 3 , 4…”
Section: Introductionmentioning
confidence: 99%
“…1 Alpha-1 antitrypsin deficiency (AATD) is a genetic condition, transmitted by autosomal codominant inheritance, caused by mutations of the SERPINA1 gene, of which more than 120 variants have been identified, and about 40% of them can cause AATD. 2 The vast majority of SERPINA1 genotypes result from combinations between the normal protease inhibitor (Pi) M allele and the most frequent deficiency alleles PiS and PiZ, namely PiMM, PiMS, PiSS, PiMZ, PiSZ and PiZZ, which roughly express 100%, 80%, 60%, 55%, 40% and 15% of serum AAT, respectively. 3,4 The Z allelic variant (Glu342Lys) is characterized by the production of a defective protein with marked conformational changes causing the formation of AAT-Z polymers that are retained within hepatocytes without being secreted into the blood, and a loss of their inhibitory capacity of 80-90%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various mutations have been identified that cause reduced serum levels of AAT, and the most common mutations are the missense mutations (Glu342Lys) Z and (Glu264Val) S. These mutations result in serum AAT concentrations of 15% in patients with homozygous ZZ mutations and 33.3% of normal levels in heterozygous SZ mutations, respectively [ 1 ]. Very low circulating AAT levels can be caused by mutants with a stop codon in SERPINA1 (null alleles, like Q 0Bellingham ) or by mutants coding for synthesis of a misfolded protein that is rapidly degraded by the endoplasmic reticulum (ER)-associated machinery (M-like alleles, such as M Procida [ 2 ] and M Heerlen [ 3 ]). Previously, we showed that serum levels of AAT are correlated with the severity of emphysema [ 4 ].…”
Section: Introductionmentioning
confidence: 99%